Acrylic acid hydrogenation catalyst and preparation method thereof
By synthesizing organic cages of specific sizes on the outer surface of the support and supporting Pd active components, the problem of insufficient stability of the propionic acid catalyst for hydrogenation of acrylic acid is solved, and the high stability and selectivity of the catalyst is achieved, and the life of the catalyst is extended.
Patent Information
- Application Number
- CN202311219823.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-09-20
AI Technical Summary
In the prior art, the Pd-based catalyst for preparing propionic acid by hydrogenation of acrylic acid has the problem of insufficient stability, especially in acidic systems, where the activity and selectivity of the catalyst will be significantly reduced after long-term use.
The catalyst stability is improved by synthesizing organic cages of specific sizes on the outer surface of the support, the size of active particles is controlled and the anchoring effect of the organic cage is used. The specific solution is to use silica gel as a support to synthesize an organic cage on its outer surface and support the active component Pd to ensure that the cage cavity size of the organic cage is between 2.7 and 3.6 nm, thereby improving the stability and selectivity of the catalyst.
Through this technical method, the stability and selectivity of the catalyst are significantly improved and the life of the catalyst is extended. Compared with traditional catalysts, the life is doubled, while maintaining efficient hydrogenation activity and selectivity.
Smart Images

Figure BDA0004460256090000191 
Figure BDA0004460256090000201 
Figure BDA0004460256090000202
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of propionic acid synthesis, and in particular to an acrylic acid hydrogenation catalyst and a preparation method thereof. Background Art
[0002] Propionic acid is an important fine chemical and basic chemical raw material, widely used in food, feed, rubber, plastic, paint, coating, fragrance, medicine, pesticide and other fields. Propionic acid is not only an effective preservative, but also one of the important fine chemical raw materials. Propionic acid can be used to prepare other organic chemical raw materials and intermediates, such as propionic anhydride, propionyl chloride, etc.
[0003] The demand for propionic acid has grown rapidly in recent years, and this growth trend is expected to continue in the next few years. In the 1950s, foreign countries developed a process for synthesizing acetic acid with the oxidation of light hydrocarbons as a byproduct of propionic acid. In the 1960s, the ethylene carbonylation method was developed. Since then, various technologies such as propionaldehyde oxidation, ethanol carbonylation, acrylonitrile and n-propanol oxidation have been developed. At present, the domestic propionic acid preparation technology still uses the traditional light hydrocarbon oxidation method, but the reaction liquid composition of this method is complex, and separation and purification require special measures and large investment; therefore, it is very necessary to develop new and advanced propionic acid production methods.
[0004] As an important organic synthetic raw material and synthetic resin monomer, acrylic acid has an increasingly widening application range. More than 85% of acrylic acid is prepared by the relatively economical propylene oxidation method, which is also the preferred method for large-scale production. At present, the world has formed the ability to produce cheap acrylic acid. Therefore, the technology of preparing propionic acid by hydrogenation of acrylic acid is expected to become a cheap technology for producing propionic acid.
[0005] At present, there are few reports on the preparation of propionic acid by hydrogenation of acrylic acid. Although some progress has been made in Pd-based catalysts, these catalysts all have the problem of insufficient stability. For example, Chinese patent document CN114230453A reports a production method for synthesizing propionic acid by one-step hydrogenation, in which the catalyst adopts Pd-Pt catalyst to react at a reaction temperature of 60-200°C, and the acrylic acid conversion rate can reach 99%. However, the Pd-based catalyst in this technology still has problems such as poor catalytic stability and easy polymerization of acrylic acid under reaction conditions. Chinese patent document CN114644552A reports a nano-supported ruthenium carbon catalyst for the hydrogenation of acrylic acid to propionic acid, and the raw material acrylic acid conversion rate and product propionic acid yield both reach more than 99%. However, in this technology, only active metal rhenium is loaded on activated carbon to catalyze hydrogenation, but the stability of the catalyst is insufficient and the industrial application value is not high.
[0006] In view of the problem of insufficient stability of the Pd-based catalyst for preparing propionic acid by hydrogenation of acrylic acid, Chinese patent document CN114160196A reports a method for preparing a Pd cluster catalyst, which is to confine the aggregation of Pd clusters by synthesizing an organic cage, and obtain good hydrogenation activity, selectivity and stability in the alkynol hydrogenation reaction. Although the stability of the catalyst is improved, the catalyst is applied to the hydrogenation of alkynols, the reaction system is not strongly acidic, and the stability requirements of the catalyst are not high. Moreover, the size of the organic cage prepared by the method is small, and the catalyst particle size is small, and the catalyst separation is difficult, which is not conducive to large-scale industrial application.
[0007] Chinese patent document CN111203217A reports a hydrogenation catalyst, which is a three-dimensional organic cage carrier with tetraaldehyde tetraphenylethylene as the skeleton and Pd 2+ 、Re 2+ The organic cage / nanoparticle complex can play a synergistic or tandem catalytic role in the reaction system of hydrogenating tert-butylphenol to prepare cis-tert-butyl cyclohexanol, and has not only good catalytic activity but also high selectivity for the target product. However, the organic cage used in this scheme is mainly used to disperse the particle size of the active center, thereby improving the catalytic activity, but whether its stability is improved remains to be verified. Summary of the invention
[0008] In view of the problems existing in the prior art and the directions for improvement, the present invention provides an acrylic acid hydrogenation catalyst to solve the problem of insufficient stability of hydrogenation catalysts in acidic systems in the prior art. The acrylic acid hydrogenation catalyst provided by the present invention controls the size of active particles by synthesizing an "organic cage" of a specific size on the outer surface of the carrier, and at the same time utilizes the anchoring effect of the organic cage to improve the stability of the catalyst, so that the catalyst can be used in an acrylic acid hydrogenation system.
[0009] To achieve the above object, the present invention adopts the following technical solutions:
[0010] An acrylic acid hydrogenation catalyst, wherein the active component includes Pd, and the carrier is silica gel or mainly silica gel; the outer surface of the carrier has an organic cage with a regular structure, the active component is uniformly loaded in the organic cage, and the cage cavity size of the organic cage is 2.7 to 3.6 nm;
[0011] The specific surface area of the acrylic acid hydrogenation catalyst is 50 to 100 m 2 / g, based on 100% by mass of the acrylic acid hydrogenation catalyst, the Pd content is 0.2% to 0.4%.
[0012] The propylene hydrogenation catalyst provided by the present invention has active components loaded in an organic cage on the outer surface of a carrier. Due to the limitation of the physical size of the organic cage, the maximum size of the active center is the size of the cage, so the size of the active center is also uniform. Under this specific size, the requirement of acrylic acid hydrogenation activity can be met, and the organic cage can well block and fix the active center, effectively reducing the agglomeration of the active center, thus greatly improving the stability of the catalyst and prolonging the life of the catalyst. The life of the catalyst is 1 times longer than that of a traditional catalyst. At the same time, because the organic cage is located on the outer surface of the catalyst, the influence of internal diffusion on the catalytic reaction is avoided, so that the selectivity of the catalyst is very good.
[0013] Optionally, in the acrylic acid hydrogenation catalyst, the content of silica gel in the carrier is greater than 80%, and the carrier may also contain metal oxides, such as magnesium oxide, titanium oxide, etc. The carrier may be spherical, cylindrical, clover-shaped, four-leaf clover-shaped, etc.
[0014] Optionally, in the acrylic acid hydrogenation catalyst, the organic cage is located within 0.08 mm extending from the outer surface of the carrier toward the center.
[0015] Optionally, in the acrylic acid hydrogenation catalyst, the organic cage is prepared by an aldehyde-amine condensation reaction between an aromatic diamine compound and tri(4-formylphenyl)amine; preferably, the aromatic diamine compound is selected from 4,4"-diaminoquaternaryl, or 4,4"-diaminoquaternaryl substituted by Rm, and the Rm is selected from at least one of halogen (F, Cl, Br, I), C1-C5 straight chain or linear alkyl (methyl, ethyl, propyl, isopropyl, butyl, tert-butyl, pentyl, etc.).
[0016] The present invention also provides a method for preparing the acrylic acid hydrogenation catalyst, comprising the following steps:
[0017] 1) completely polymerizing the hydrophilic polymerizable monomer in the pores of the carrier without decomposing the generated polymer, and controlling the polymer to occupy more than 80% of the pore volume of the carrier (during the experiment, the mass or volume of the required polymerizable monomer can be converted according to the mass of the carrier combined with the water absorption rate, pore volume and other related parameters of the carrier, so as to control the polymer to occupy more than 80% of the pore volume of the carrier), to obtain a semi-finished catalyst A;
[0018] 2) dissolving tri(4-formylphenyl)amine and a catalyst in a solvent, and mixing the solvent with the semi-finished catalyst A to obtain a mixed solution; adding a solution of an aromatic diamine compound dropwise to the mixed solution to carry out an aldehyde-amine condensation reaction to form an organic cage; after the reaction is completed, pouring out the residual liquid, washing with alcohol and deionized water, and drying, respectively, to obtain a semi-finished catalyst B;
[0019] 3) under stirring, dripping a solution of an organic palladium compound (the organic palladium compound is completely dissolved in a good solvent, and the good solvent is a solvent that can dissolve the organic palladium compound) into a mixture of the semi-finished catalyst B and an alcohol, and after the organic palladium compound is completely loaded (that is, the organic palladium compound is completely loaded in the organic cage of the semi-finished catalyst B, and the surface of the semi-finished catalyst B no longer changes color, which means it is completely loaded), washing with deionized water, drying, and calcining at ≤400° C. to completely decompose the polymer, thereby obtaining a semi-finished catalyst C;
[0020] 4) mixing the semi-finished catalyst C with a reducing agent to reduce palladium, and after the palladium is completely reduced, decanting the solution, washing with deionized water, and drying to obtain an acrylic acid hydrogenation catalyst;
[0021] Wherein, the molar ratio of the tri(4-formylphenyl)amine to the aromatic diamine compound is 1:1.1-2.2.
[0022] In the above step 3), the purpose of forming a mixture of the semi-finished catalyst B and the alcohol is to disperse the semi-finished catalyst B and improve the uniformity of the loading of the organic palladium compound.
[0023] When traditional hydrogenation catalysts catalyze olefin hydrogenation reactions, the activation occurs on the main active center Pd, and during the catalyst preparation process, the activation is a high-temperature roasting process, during which metal salts generally decompose into metal oxides, and the oxides form clusters. However, the aggregation of active components during the roasting process is a random process, and only active centers with a normal distribution of most scales of 1-5nm can be formed. Active centers are prone to agglomeration, and the activity of the catalyst will decrease after agglomeration, and the stability of the catalyst is insufficient.
[0024] The idea of the present invention to solve the above-mentioned catalyst clusters is as follows: in order to make the active center located on the outer surface of the catalyst, it is necessary to synthesize the organic cage on the outer surface of the catalyst. Specifically, before the synthesis of the organic cage, an easily decomposable organic polymer is formed in situ inside the carrier, so that it occupies the internal pores of the carrier, and the organic cage is synthesized in the pores close to the outer surface (ensuring that the organic cage is located on the outer surface of the carrier). After the synthesis of the organic cage with uniform size, the active component organic palladium compound (organic precursor salt of Pd) is loaded in the organic cage, and the anchoring effect of the organic cage is utilized to prevent the agglomeration of the active component and the diffusion into the interior of the carrier; then, at a decomposition temperature lower than the organic cage, the organic polymer in the pores of the carrier is decomposed, and finally a catalyst with high stability and high activity is obtained, and at the same time, the water resistance and acid resistance of the catalyst are improved, which is of great significance to further extend the operation time of the catalyst.
[0025] Optionally, in step 4) of the method for preparing an acrylic acid hydrogenation catalyst provided by the present invention, the semi-finished catalyst C can be mixed with a solvent and then mixed with the reducing agent. After the palladium is completely reduced, the solution is poured off, washed with deionized water, and dried to obtain an acrylic acid hydrogenation catalyst; preferably, the reducing agent is selected from methanol, formaldehyde, formic acid, ethanol, acetaldehyde or hydrazine hydrate, and the solvent is selected from ethanol or deionized water. The reducing agent can be directly added or added dropwise to the mixture of the semi-finished catalyst C and the solvent.
[0026] Specifically, as in step 4), the semi-finished catalyst C can be fully mixed with a reducing agent, and after the palladium is completely reduced, the solution is poured off, washed with deionized water, and dried to obtain an acrylic acid hydrogenation catalyst; or
[0027] After the semi-finished catalyst C is fully mixed with a solvent (deionized water or ethanol), a reducing agent is added successively for stirring reduction. After palladium is completely reduced, the solution is poured off, the mixture is washed with deionized water, and dried to obtain an acrylic acid hydrogenation catalyst.
[0028] Optionally, in the method for preparing the acrylic acid hydrogenation catalyst provided by the present invention, the mass ratio of palladium in the organic palladium compound to the tri(4-formylphenyl)amine is 2 to 14:1.
[0029] By limiting the molar ratio of tri(4-formylphenyl)amine to the aromatic diamine compound and combining the mass ratio of palladium in the organic palladium compound to the tri(4-formylphenyl)amine, the mass ratio of palladium in the organic cage and the organic palladium compound is indirectly limited, thereby further improving the uniformity of palladium distribution in the organic cage.
[0030] Optionally, in the method for preparing the acrylic acid hydrogenation catalyst provided by the present invention, in step 1), the volume of the hydrophilic polymerizable monomer is 80%-100%, preferably 80%-95% of the pore volume of the carrier.
[0031] Optionally, in the preparation method of the acrylic acid hydrogenation catalyst provided by the present invention, in step 1), the hydrophilic polymerizable monomer is selected from organic compounds containing a carbonyl group, a carboxyl group or a carbon-carbon double bond, and is capable of polymerization or condensation, and the specific polymerization or condensation temperature and conditions can be adjusted according to the polymerization monomer used; preferably, the hydrophilic polymerizable monomer is selected from acrylic acid, acrylic acid ester or lactic acid, and conventional polymerization conditions in the industry can be used.
[0032] Optionally, in the method for preparing an acrylic acid hydrogenation catalyst provided by the present invention, in step 2), the catalyst is a halogenated acetic acid, preferably fluoroacetic acid or chloroacetic acid, more preferably trifluoroacetic acid or dichloroacetic acid;
[0033] The mass ratio of the tri(4-formylphenyl)amine to the catalyst is 2000-6000:1.
[0034] Optionally, in the method for preparing an acrylic acid hydrogenation catalyst provided by the present invention, in step 3), the organic palladium compound is selected from palladium acetate or palladium acetylacetonate.
[0035] Optionally, in the method for preparing the acrylic acid hydrogenation catalyst provided by the present invention, in step 4), the reducing agent is selected from methanol, formaldehyde, formic acid, ethanol, acetaldehyde or hydrazine hydrate.
[0036] In the preparation method of the acrylic acid hydrogenation catalyst provided by the present invention, the solvent involved and the solvent used in the solution are not specifically limited, and they only need to be able to dissolve the corresponding substances, such as tri(4-formylphenyl)amine and the catalyst dissolved in the solvent, the solution of the aromatic diamine compound, and the solution of the organic palladium compound. The solvent used in these three solutions only needs to be able to dissolve the corresponding solutes. The solvent recommended by the present invention is an alkyl halide, preferably a fluoroalkane, a chloroalkane or a bromoalkane, and more preferably ethylene dichloride or chloroform. The specific solvent can be adjusted according to the properties of the actual compound. For example, when the organic palladium compound is palladium chloride or palladium acetate, hydrochloric acid or glacial acetic acid can be used for dissolution.
[0037] In the preparation method of the acrylic acid hydrogenation catalyst provided by the present invention, the parameters such as the polymerization temperature and time in step 1) can be adjusted according to the properties and dosage of the actual polymerization monomers, as long as the polymerizable monomers can be completely polymerized and do not decompose during the polymerization process. The conditions for the aldehyde-amine condensation reaction of tri(4-formylphenyl)amine and the aromatic diamine compound in step 2) can be adjusted according to the actual material ratio, the catalyst used, etc., as long as the aldehyde-amine condensation reaction can be carried out to form an organic cage structure on the outer surface of the carrier. In step 3), the parameters of the organic palladium compound loading can be adjusted according to the concentration of the actual organic palladium compound solution, etc., so as to achieve the effective loading of the organic palladium compound; the calcination temperature requires that the polymer is completely decomposed under the premise of ensuring that the pore structure of the carrier is not destroyed (i.e., less than 400°C). In step 4), the parameters for reducing palladium can be conventional in the industry, and can be adjusted according to actual conditions. The parameters for drying in each specific step can be conventional in the industry.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] Beneficial effect 1: The acrylic acid hydrogenation catalyst provided by the present invention adopts silica gel or mainly silica gel as a carrier, arranges an organic cage on the outer surface of the carrier, combines to limit the cage cavity size of the organic cage, and loads active components including palladium in the organic cage, and utilizes the anchoring effect of the organic cage itself to effectively prevent the agglomeration and migration of the active components, thereby greatly improving the stability of the catalyst in the acidic system: the evaluation results of 1000h show that the hydrogenation activity and selectivity are basically not reduced.
[0040] Beneficial effect 2: The preparation method of the acrylic acid hydrogenation catalyst provided by the present invention first occupies most of the pores inside the carrier with a decomposable polymer to ensure that the organic cage grows on the outer surface of the carrier in the later stage, and after the active component Pd and the like are loaded in the organic cage, the polymer is heated and decomposed to release the pores inside the carrier (the pores occupied by the polymer) under the premise of ensuring that the pore structure of the catalyst is not destroyed, and the cage cavity size of the organic cage is matched with the optimal active center stacking size required for the hydrogenation of acrylic acid by controlling the proportion of the decomposable polymer monomer synthesized in situ (that is, the size of the active center is regulated by the cage cavity size of the organic cage). In this way, the decomposable polymer can be effectively used to prevent the Pd particles from migrating into the interior of the carrier, and the organic cage on the outer surface of the carrier is used to control the lateral agglomeration of the Pd grains, so that the active components are evenly distributed in the organic cage. The catalyst has extremely high activity and selectivity. The evaluation results show that the conversion rate of acrylic acid hydrogenation is more than 95%, and the selectivity is 100%. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a simulation diagram of the organic cage in the acrylic acid hydrogenation catalyst prepared in Example 6. DETAILED DESCRIPTION
[0042] The following is a detailed description of the embodiments of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and process are given, but the protection scope of the present invention is not limited to the following embodiments. The experimental methods in the following embodiments without specifying specific conditions are usually carried out under conventional conditions.
[0043] Source of raw materials or equipment:
[0044] BET tester, Micromeritics, USA, was used to measure the specific surface area and the size of the organic cage.
[0045] Digital microscope, Shangguang Fifth Factory, 19JC digital universal tool microscope.
[0046] A240FS atomic absorption spectrometer and Agilent 7890A gas chromatograph are used to determine the Pd content in the catalyst; and to measure the hydrogen, acrylic acid and propionic acid contents at the reactor outlet and inlet when the catalyst is used for performance evaluation of acrylic acid hydrogenation reaction.
[0047] The technical solution of the present invention is further described below through specific embodiments, but they are not intended to limit the technical solution of the present invention.
[0048] Example 1
[0049] Carrier: Commercially available spherical silica carrier with a diameter of 2 mm was used. After calcination at 1050°C for 4 hours, the water absorption rate and pore volume were 0.65 m 3 / g, specific surface area is 50m 2 Weigh 100 g of the carrier.
[0050] Catalyst preparation:
[0051] (1) Weigh 73.5 g of lactic acid and mix with 100 g of the calcined carrier, and keep the mixture at 160° C. for 10 hours to obtain a semi-finished catalyst A;
[0052] (2) 0.2 g of tri(4-formylphenyl)amine and 0.1 mg of dichloroacetic acid were mixed and dissolved in 60 ml of dichloroethane, then mixed with semi-finished catalyst A, stirred and a mixed solution of 0.234 g of 4,4"-diaminoquaternary biphenyl and 10 ml of trichloroethane was added dropwise, the mixture was allowed to stand at room temperature for 200 hours, the residual liquid was poured out, washed with ethanol and deionized water respectively, and dried at 120°C to obtain semi-finished catalyst B;
[0053] (3) 1.145 g of palladium acetylacetonate was dissolved in 50 mL of chloroform. After the palladium acetylacetonate was completely dissolved, the semi-finished catalyst B was immersed in 50 mL of ethanol. The prepared palladium acetylacetonate chloroform solution was added dropwise to the mixture of the semi-finished catalyst B and ethanol. The mixture was stirred for 30 hours, allowed to stand for 5 hours, the solution was decanted, the mixture was washed with deionized water, dried at 120° C., and calcined at 360° C. for 8 hours to obtain a semi-finished catalyst C.
[0054] (4) The semi-finished catalyst C was immersed in an ethanol solution, stirred at 75° C. for 1 hour, the solution was decanted, the catalyst was washed with deionized water, and dried at 120° C. to obtain an acrylic acid hydrogenation catalyst.
[0055] Comparative Example 1
[0056] Carrier: The same carrier as in Example 1 was used;
[0057] The preparation process of the catalyst is similar to that of Example 1, except that lactic acid is not added in step (1).
[0058] Catalyst preparation:
[0059] (1) Weigh 100 g of the calcined support, referred to as A1;
[0060] (2) 0.2 g of tri(4-formylphenyl)amine and 0.1 mg of dichloroacetic acid were mixed and dissolved in 60 ml of dichloroethane, then mixed with A1, stirred and a mixed solution of 0.234 g of 4,4"-diaminoquaternary biphenyl and 10 ml of trichloroethane was added dropwise, the mixture was allowed to stand at room temperature for 200 hours, the residual liquid was poured out, and the mixture was washed with ethanol and deionized water respectively, and dried at 120°C to obtain a semi-finished catalyst B1;
[0061] (3) 1.145 g of palladium acetylacetonate was dissolved in 50 mL of chloroform. After the palladium acetylacetonate was completely dissolved, the semi-finished catalyst B1 was immersed in 50 mL of ethanol. The prepared palladium acetylacetonate chloroform solution was dropwise added to the mixture of the semi-finished catalyst B1 and ethanol. The mixture was stirred for 30 hours. The mixture was allowed to stand for 5 hours. The solution was decanted, washed with deionized water, dried at 120° C., and calcined at 360° C. for 8 hours to obtain the semi-finished catalyst C1.
[0062] (4) The semi-finished catalyst C was immersed in an ethanol solution, stirred at 75° C. for 1 hour, the solution was decanted, the catalyst was washed with deionized water, and dried at 120° C. to obtain an acrylic acid hydrogenation catalyst.
[0063] Example 2
[0064] Catalyst carrier: A commercially available spherical silica gel carrier with a diameter of 2 mm was used. After calcination at 850°C for 4 hours, the water absorption pore volume was measured to be 0.5 ml / g and the specific surface area was 100.5 m 2 Weigh 100 g of the carrier.
[0065] Catalyst preparation:
[0066] (1) Weigh 40.6 g of an aqueous solution containing 30% acrylic acid, 0.02 g of potassium hypophosphite monohydrate, 0.045 g of copper acetate monohydrate, and 0.3 ml of 35% hydrogen peroxide as an initiator, mix them evenly, add 100 g of the calcined carrier, and after the solution is completely absorbed, transfer it to a reflux bottle, heat it to 80° C. with stirring, and keep it at this temperature for 1 hour to obtain a semi-finished catalyst D;
[0067] (2) 0.0143 g of tri(4-formylphenyl)amine and 0.0023 mg of dichloroacetic acid were mixed and dissolved in 50 ml of dichloroethane, and then mixed with semi-finished catalyst D, stirred and a mixed solution of 0.0316 g of 4,4"-diaminoquaternary biphenyl and 10 ml of dichloroethane was added dropwise. After the addition was completed, the mixture was allowed to stand at room temperature for 200 hours, the residual liquid was poured out, and the mixture was washed with ethanol and deionized water respectively, and dried at 60°C to obtain semi-finished catalyst E;
[0068] (3) 0.422 g of palladium acetate was dissolved in 50 mL of glacial acetic acid. After the palladium acetate was completely dissolved, an acetic acid solution of palladium acetate was obtained. The semi-finished catalyst E was immersed in 50 mL of ethanol. Then, the prepared palladium acetate solution was added dropwise to the mixture of the semi-finished catalyst E and ethanol. The mixture was stirred for 30 hours. The solution was decanted, washed with deionized water, dried at 120° C. to remove the solvent, and then calcined at 400° C. for 8 hours to obtain a semi-finished catalyst F.
[0069] (4) The semi-finished catalyst F was immersed in deionized water, and 5 ml of 5% hydrazine hydrate solution was added dropwise. The mixture was stirred at room temperature for 1 hour, the solution was decanted, the mixture was washed with deionized water, and dried at 100° C. to obtain an acrylic acid hydrogenation catalyst.
[0070] Comparative Example 2
[0071] Catalyst carrier: Same as Example 2.
[0072] The preparation process of the catalyst is similar to that of Example 2, except that the amount of 4,4"-diaminoquaternaryl is different.
[0073] Catalyst preparation:
[0074] (1) Weigh 40.6 g of an aqueous solution containing 30% acrylic acid, 0.02 g of potassium hypophosphite monohydrate, 0.045 g of copper acetate monohydrate, and 0.3 ml of 35% hydrogen peroxide as an initiator, mix them evenly, add 100 g of the calcined carrier, and after the solution is completely absorbed, transfer it to a reflux bottle, heat it to 80° C. with stirring, and keep it at this temperature for 1 hour to obtain a semi-finished catalyst D1;
[0075] (2) 0.0143 g of tri(4-formylphenyl)amine and 0.0023 mg of dichloroacetic acid were mixed and dissolved in 50 ml of dichloroethane, and then mixed with the semi-finished catalyst D1, and a mixed solution of 0.0129 g of 4,4"-diaminoquaternary biphenyl and 10 ml of dichloroethane was added dropwise with stirring. After the addition was completed, the mixture was allowed to stand at room temperature for 200 hours, the residual liquid was poured out, and the mixture was washed with ethanol and deionized water respectively, and dried at 60°C to obtain the semi-finished catalyst E1;
[0076] (3) 0.422 g of palladium acetate was dissolved in 50 mL of glacial acetic acid. After the palladium acetate was completely dissolved, an acetic acid solution of palladium acetate was obtained. The semi-finished catalyst E1 was immersed in 50 mL of ethanol. Then, the prepared palladium acetate solution was added dropwise to the mixture of the semi-finished catalyst E and ethanol. The mixture was stirred for 30 hours. The solution was decanted, washed with deionized water, dried at 120° C. to remove the solvent, and then calcined at 400° C. for 8 hours to obtain the semi-finished catalyst F1.
[0077] (4) The semi-finished catalyst F1 was immersed in deionized water, and 5 ml of 5% hydrazine hydrate solution was added dropwise. The mixture was stirred at room temperature for 1 hour, the solution was decanted, the mixture was washed with deionized water, and dried at 100° C. to obtain an acrylic acid hydrogenation catalyst.
[0078] Example 3
[0079] Catalyst carrier: A commercially available spherical silica gel carrier with a diameter of 2.5 mm was used. After calcination at 980°C for 4 hours, the water absorption pore volume was measured to be 0.58 ml / g and the specific surface area was 71.2 m 2 Weigh 100 g of the carrier.
[0080] Catalyst preparation:
[0081] (1) Weighing 62.11 g of lactic acid and mixing it with 100 g of the calcined carrier, the mixture was kept at 160° C. for 10 hours to obtain a semi-finished catalyst G;
[0082] (2) Weigh 0.0375 g of tri(4-formylphenyl)amine and 0.0125 mg of dichloroacetic acid, mix them, dissolve them in 50 ml of dichloroethane, and then mix them with the semi-finished catalyst G. Stir and dropwise add a mixed solution of 0.0542 g of 4,4"-diaminoquaternaryl and 10 ml of dichloroethane. After the dropwise addition is complete, let stand at room temperature for 200 hours, pour out the residual liquid, wash with ethanol and deionized water respectively, and dry at 80°C to obtain the semi-finished catalyst H;
[0083] (3) 0.63 g of palladium acetate was dissolved in 50 ml of glacial acetic acid. After the palladium acetate was completely dissolved, a palladium acetate solution was obtained. The semi-finished catalyst H was immersed in 50 ml of ethanol. The prepared palladium acetate solution was added dropwise to the mixture of the semi-finished catalyst H and ethanol. The mixture was stirred for 10 hours. The mixture was allowed to stand for 3 hours. The solution was decanted, washed with deionized water, dried at 120° C., and calcined at 350° C. for 8 hours to obtain a semi-finished catalyst J.
[0084] (4) Add 50 ml of deionized water to the semi-finished catalyst J, then dropwise add 20 ml of formaldehyde solution, heat to boiling and stir for 10 minutes, decant the solution, wash with deionized water, and dry at 120° C. to obtain the desired catalyst.
[0085] Comparative Example 3
[0086] Catalyst carrier: Same as Example 3.
[0087] The preparation process of the catalyst is similar to that of Example 3, except that the aromatic diamine compound used in the comparative example is diphenyl diamine.
[0088] Catalyst preparation:
[0089] (1) Weighing 62.11 g of lactic acid and mixing it with 100 g of the calcined carrier, the mixture was kept at 160° C. for 10 hours to obtain a semi-finished catalyst G1;
[0090] (2) Weigh 0.0375 g of tri(4-formylphenyl)amine and 0.0125 mg of dichloroacetic acid, mix them, dissolve them in 50 ml of dichloroethane, and then mix them with the semi-finished catalyst G1. Stir and dropwise add a mixed solution of 0.0296 g of diphenyl diamine and 10 ml of dichloroethane. After the dropwise addition is complete, let stand at room temperature for 200 hours, pour out the residual liquid, wash with ethanol and deionized water, respectively, and dry at 80° C. to obtain the semi-finished catalyst H1;
[0091] (3) 0.63 g of palladium acetate was dissolved in 50 ml of glacial acetic acid. After the palladium acetate was completely dissolved, a palladium acetate solution was obtained. The semi-finished catalyst H1 was immersed in 50 ml of ethanol. The prepared palladium acetate solution was added dropwise to the mixture of the semi-finished catalyst H1 and ethanol. The mixture was stirred for 10 hours. The mixture was allowed to stand for 3 hours. The solution was decanted, washed with deionized water, dried at 120° C., and calcined at 350° C. for 8 hours to obtain the semi-finished catalyst J1.
[0092] (4) Add 50 ml of deionized water to the semi-finished catalyst J1, then dropwise add 20 ml of formaldehyde solution, heat to boiling and stir for 10 minutes, decant the solution, wash with deionized water, and dry at 120° C. to obtain the desired catalyst.
[0093] Example 4
[0094] Carrier: A commercially available spherical silica gel carrier with a diameter of 3 mm was used. After calcination at 950°C for 4 hours, the water absorption rate, pore volume, and specific surface area were 0.60 ml / g and 80.8 m 2 Weigh 100 g of the carrier.
[0095] Catalyst preparation:
[0096] (1) Weighing 65.69 g of lactic acid and mixing it with 100 g of the calcined carrier, the mixture was kept at 160° C. for 2 hours to obtain a semi-finished catalyst K;
[0097] (2) 0.058 g of tri(4-formylphenyl)amine and 0.0116 mg of trifluoroacetic acid were mixed and dissolved in 50 ml of dichloroethane, and then mixed with the semi-finished catalyst K. After stirring, a mixed solution of 0.1 g of 2-methyl-4,4"-diaminoquaternaryl and 10 ml of dichloroethane was added dropwise. After the addition was completed, the mixture was allowed to stand at room temperature for 80 hours, the residual liquid was poured out, and the mixture was washed with ethanol and deionized water respectively, and dried at 100° C. to obtain the semi-finished catalyst M;
[0098] (3) Dissolve 1.0 g of palladium acetylacetonate in 50 ml of chloroform. After the palladium acetylacetonate is completely dissolved, a palladium acetylacetonate solution is obtained. The semi-finished catalyst M is immersed in 50 ml of ethanol. The prepared palladium acetylacetonate solution is added dropwise to the mixture of the semi-finished catalyst M and ethanol. Stir for 12 hours. Let stand for 6 hours. Pour off the solution. Wash with deionized water. Dry at 90° C. and calcine at 380° C. for 4 hours to obtain the semi-finished catalyst N.
[0099] (4) Add 50 ml of ethanol solution to the semi-finished catalyst N, then dropwise add 20 ml of formic acid solution, stir at 25°C for 20 minutes, decant the solution, wash with ethanol, and dry at 100°C to obtain an acrylic acid hydrogenation catalyst.
[0100] Comparative Example 4
[0101] Carrier: Same as Example 4.
[0102] The preparation process of the catalyst is similar to that of Example 4, except that the polymerization temperature of lactic acid in Example 4 is 280°C.
[0103] Catalyst preparation:
[0104] (1) Weighing 65.69 g of lactic acid and mixing it with 100 g of the calcined carrier, the mixture was kept at 280° C. for 2 hours to obtain a semi-finished catalyst K1;
[0105] (2) 0.058 g of tri(4-formylphenyl)amine and 0.0116 mg of trifluoroacetic acid were mixed and dissolved in 50 ml of dichloroethane, and then mixed with the semi-finished catalyst K1, and a mixed solution of 0.1 g of 2-methyl-4,4"-diaminoquaternaryl and 10 ml of dichloroethane was added dropwise with stirring. After the addition was completed, the mixture was allowed to stand at room temperature for 80 hours, the residual liquid was poured out, and the mixture was washed with ethanol and deionized water respectively, and dried at 100°C to obtain the semi-finished catalyst M1;
[0106] (3) Dissolve 1.0 g of palladium acetylacetonate in 50 ml of chloroform. After the palladium acetylacetonate is completely dissolved to obtain a palladium acetylacetonate solution, immerse the semi-finished catalyst M1 in 50 ml of ethanol, and drop the prepared palladium acetylacetonate solution into the mixture of the semi-finished catalyst M1 and ethanol. Stir for 12 hours, let stand for 6 hours, pour off the solution, wash with deionized water, dry at 90° C., and calcine at 380° C. for 4 hours to obtain a semi-finished catalyst N1.
[0107] (4) Add 50 ml of ethanol solution to the semi-finished catalyst N1, then dropwise add 20 ml of formic acid solution, stir at 25°C for 20 minutes, decant the solution, wash with ethanol, and dry at 100°C to obtain an acrylic acid hydrogenation catalyst.
[0108] Example 5
[0109] Carrier: A commercially available spherical silica gel-titanium oxide carrier was used, with a titanium oxide content of 20% and a diameter of 4 mm. After calcination at 900°C for 4 hours, the water absorption pore volume was 0.62 ml / g and the specific surface area was 89.2 m 2 Weigh 100 g of the carrier.
[0110] Catalyst preparation:
[0111] (1) Weigh 55.37 g of 25% acrylic acid solution, 0.015 g of potassium hypophosphite monohydrate, 0.028 g of copper acetate monohydrate, and 0.2 ml of 30% hydrogen peroxide as an initiator, mix them evenly, add 100 g of the calcined carrier, and after the solution is completely absorbed, transfer it to a reflux bottle, heat it to 85° C. with stirring, and keep it at this temperature for 1 hour to obtain a semi-finished catalyst O;
[0112] (2) 0.0625 g of tri(4-formylphenyl)amine and 0.0125 mg of trichloroacetic acid were mixed and dissolved in 50 ml of dichloroethane, then mixed with the semi-finished catalyst O, stirred and a mixed solution of 0.115 g of 4,4"-diaminoquaternary biphenyl and 10 ml of trichloroethane was added dropwise. After the addition was completed, the mixture was allowed to stand at room temperature for 150 hours, the residual liquid was poured out, and the mixture was washed with ethanol and deionized water respectively, and dried at 90°C to obtain the semi-finished catalyst P;
[0113] (3) Dissolve 0.716 g of palladium acetylacetonate in 50 ml of chloroform until the palladium acetylacetonate is completely dissolved to obtain a palladium acetylacetonate solution. Immerse the semi-finished catalyst P in 50 ml of ethanol, drop the prepared palladium acetylacetonate solution into the mixture of the semi-finished catalyst P and ethanol, stir for 20 hours, let stand for 4 hours, pour off the solution, wash with deionized water, dry at 110° C., and calcine at 400° C. for 2 hours to obtain a semi-finished catalyst Q;
[0114] (4) The semi-finished catalyst Q was immersed in 50 ml of ethanol, and then 25 ml of acetaldehyde was added dropwise. The mixture was stirred at 70° C. for 2 hours. The solution was decanted, washed with deionized water, and dried at 120° C. to obtain an acrylic acid hydrogenation catalyst.
[0115] Comparative Example 5
[0116] Carrier: Same as Example 5
[0117] Catalyst preparation: The catalyst prepared in this comparative example has the same active component content as that in Example 5. The catalyst is prepared by a conventional method, and the specific steps are as follows:
[0118] (1) Weigh 0.42 g of palladium chloride and dissolve it in hydrochloric acid. Dilute the solution to 62 ml with deionized water, adjust the pH to 2.5, mix with 100 g of the calcined support, stir until the solution is completely absorbed, dry at 90° C., and calcine at 500° C. for 4 h to obtain a semi-finished catalyst O1;
[0119] (2) The semi-finished catalyst O1 was immersed in 50 ml of ethanol, and then 25 ml of acetaldehyde was added dropwise. The mixture was stirred at 70° C. for 2 hours. The solution was decanted, washed with deionized water, and dried at 120° C. to obtain an acrylic acid hydrogenation catalyst.
[0120] Example 6
[0121] Carrier: A commercially available toothed ball silica gel-magnesium oxide carrier was used, with a magnesium oxide content of 5% and a diameter of 3 mm. After calcination at 1030°C for 4 hours, the water absorption rate, pore volume, and specific surface area were 0.54 ml / g and 60.1 m 2 Weigh 100 g of the carrier.
[0122] Catalyst preparation:
[0123] (1) Weigh 54.6 g of lactic acid and mix with 100 g of the calcined carrier, and keep the mixture at 170° C. for 2 hours to obtain a semi-finished catalyst R;
[0124] (2) 0.11 g of tri(4-formylphenyl)amine and 0.044 mg of trifluoroacetic acid were mixed and dissolved in 50 ml of dichloroethane, then mixed with the semi-finished catalyst R, stirred and a mixed solution of 0.25 g of 3-chloro-4,4"-diaminoquaternaryl and 10 ml of dichloroethane was added dropwise, and allowed to stand at room temperature for 180 hours. The residue was poured out, washed with ethanol and deionized water respectively, and dried at 60°C to obtain the semi-finished catalyst S;
[0125] (3) 0.696 g of palladium acetate was dissolved in 50 ml of chloroform, and the palladium acetate was completely dissolved to obtain a palladium acetate solution. The semi-finished catalyst S was immersed in 50 ml of ethanol, and the prepared palladium acetate solution was added dropwise to the mixture of the semi-finished catalyst S and ethanol, and stirred for 15 hours, and allowed to stand for 4 hours, and the solution was decanted, washed with deionized water, dried at 120° C., and calcined at 400° C. for 2 hours to obtain a semi-finished catalyst T.
[0126] (4) The semi-finished catalyst T was immersed in 60 ml of deionized water, and then 5 ml of 5% hydrazine hydrate solution was added dropwise. The mixture was stirred at room temperature for 1 hour, the solution was decanted, the mixture was washed with deionized water, and dried at 120° C. to obtain an acrylic acid hydrogenation catalyst.
[0127] Figure 1 is a simulation diagram of the organic cage in the acrylic acid hydrogenation catalyst prepared in this embodiment, Figure 1It can be seen that the size range of the organic cage is 2.91 to 3.53 nm, which is consistent with the result measured by BET measurement instrument.
[0128] Comparative Example 6
[0129] Carrier: Same as Example 6.
[0130] The preparation of the catalyst is similar to that of Example 6, except that the calcination temperature in step (3) of this comparative example is 220° C. The preparation process of the catalyst in this comparative example is as follows:
[0131] Catalyst preparation:
[0132] (1) Weighing 54.6 g of lactic acid and mixing it with 100 g of the calcined carrier, the mixture was kept at 170° C. for 2 hours to obtain a semi-finished catalyst R1;
[0133] (2) 0.11 g of tri(4-formylphenyl)amine and 0.044 mg of trifluoroacetic acid were mixed and dissolved in 50 ml of dichloroethane, then mixed with the semi-finished catalyst R, stirred and a mixed solution of 0.25 g of 3-chloro-4,4"-diaminoquaternaryl and 10 ml of dichloroethane was added dropwise, and the mixture was allowed to stand at room temperature for 180 hours. The residue was poured out, washed with ethanol and deionized water respectively, and dried at 60° C. to obtain the semi-finished catalyst S1;
[0134] (3) 0.696 g of palladium acetate was dissolved in 50 ml of chloroform, and the palladium acetate was completely dissolved to obtain a palladium acetate solution. The semi-finished catalyst S1 was immersed in 50 ml of ethanol, and the prepared palladium acetate solution was added dropwise to the mixture of the semi-finished catalyst S1 and ethanol, and stirred for 15 hours, and allowed to stand for 4 hours, and the solution was decanted, washed with deionized water, dried at 120° C., and calcined at 220° C. for 2 hours to obtain a semi-finished catalyst T1.
[0135] (4) The semi-finished catalyst T1 was immersed in 60 ml of deionized water, and then 5 ml of 5% hydrazine hydrate solution was added dropwise. The mixture was stirred at room temperature for 1 hour, the solution was decanted, the mixture was washed with deionized water, and dried at 120° C. to obtain an acrylic acid hydrogenation catalyst.
[0136] Example 7
[0137] Carrier: Spherical silica gel-magnesia carrier with a magnesium oxide content of 10% and a diameter of 2 mm. After calcination at 965°C for 4 hours, the water absorption rate, pore volume, and specific surface area are 0.54 ml / g and 75 m 2 Weigh 100 g of the carrier.
[0138] Catalyst preparation:
[0139] (1) Weigh 51.4 g of lactic acid and mix with 100 g of the calcined carrier, and keep the mixture at 165° C. for 2 hours to obtain a semi-finished catalyst U;
[0140] (2) 0.12 g of tri(4-formylphenyl)amine and 0.06 mg of trifluoroacetic acid were mixed and dissolved in 50 ml of dichloroethane, and then mixed with semi-finished catalyst U to obtain a mixture. Then, a mixed solution of 0.185 g of 4,4"-diaminoquaternaryl and 10 ml of dichloroethane was added dropwise to the mixture under stirring. The mixture was allowed to stand at room temperature for 190 hours, the residual liquid was poured out, and the mixture was washed with ethanol and deionized water respectively, and dried at 100° C. to obtain semi-finished catalyst V;
[0141] (3) dissolving 0.859 g of palladium acetylacetonate in 50 ml of benzene, and waiting for the palladium acetylacetonate to be completely dissolved to obtain a palladium acetylacetonate solution; immersing the semi-finished catalyst V in 50 ml of methanol solution, and then dropping the palladium acetylacetonate solution into the mixture of the semi-finished catalyst V and methanol, stirring for 30 hours, standing for 4 hours, decanting the solution, washing with deionized water, drying at 120° C., and calcining at 380° C. for 1 hour to obtain a semi-finished catalyst W;
[0142] (4) The semi-finished catalyst W was immersed in 60 ml of deionized water, and then 5 ml of 5% hydrazine hydrate solution was added dropwise. After the addition was completed, the mixture was stirred at room temperature for 1 hour, the solution was decanted, the mixture was washed with deionized water, and dried at 120° C. to obtain an acrylic acid hydrogenation catalyst.
[0143] Comparative Example 7
[0144] The preparation process of the acrylic acid hydrogenation catalyst provided in this comparative example is similar to that of Example 7, except that no carrier is used in this comparative example and step (1) is omitted. The specific preparation process of the acrylic acid hydrogenation catalyst in this comparative example is as follows:
[0145] (1) 0.12 g of tri(4-formylphenyl)amine and 0.06 mg of trifluoroacetic acid were mixed and dissolved in 50 ml of dichloroethane. A mixed solution of 0.185 g of diphenyl diamine and 10 ml of dichloroethane was added dropwise with stirring. The mixture was allowed to stand at room temperature for 190 hours. The residue was decanted and washed with ethanol and deionized water respectively, and dried at 100° C. to obtain a semi-finished catalyst V1.
[0146] (2) dissolving 0.859 g of palladium acetylacetonate in 50 ml of benzene, and waiting for the palladium acetylacetonate to be completely dissolved to obtain a palladium acetylacetonate solution; immersing the semi-finished catalyst V1 in 50 ml of methanol, and then dropping the palladium acetylacetonate solution into the mixture of the semi-finished catalyst V1 and methanol, stirring for 30 hours, standing for 4 hours, decanting the solution, washing with deionized water, drying at 120° C., and calcining at 380° C. for 1 hour to obtain a semi-finished catalyst W1;
[0147] (3) The semi-finished catalyst W1 was immersed in 60 g of deionized water, and then 5 ml of 5% hydrazine hydrate solution was added dropwise. After the addition was completed, it was stirred at room temperature for 1 hour, the solution was decanted, washed with deionized water, and dried at 120° C. to obtain an acrylic acid hydrogenation catalyst.
[0148] The Pd content of the acrylic acid hydrogenation catalyst prepared in each embodiment and comparative example was measured by atomic absorption spectrometry (based on the mass of the acrylic acid hydrogenation catalyst as 100%), the specific surface area and the cage cavity size of the organic cage were tested by BET measuring instrument, and the distribution thickness of palladium (i.e., the depth of the organic cage extending from the outer surface of the carrier to the center) was measured by microscope. The specific test results are shown in the following table.
[0149] Table 1
[0150]
[0151]
[0152] Note: The palladium content in Comparative Example 7 is based on the total mass of the synthesized organic cage and palladium as 100%.
[0153] Performance of catalysts used in acrylic acid hydrogenation
[0154] Evaluation method: The catalyst loading in the fixed bed single-stage reactor is 100 mL (recorded weight), the filler is 50 mL, and the liquid hourly space velocity of the reaction material is 2.0 h -1 , operating pressure 2.5MPa, hydrogen-to-oil ratio 20, reactor inlet temperature 40℃.
[0155] The acrylic acid hydrogenation catalysts prepared in the examples and comparative examples were evaluated according to the above evaluation method. The specific evaluation results are shown in the following table.
[0156] Table 2 Catalyst evaluation results
[0157]
[0158]
[0159] It can be seen from the data in Table 1 and Table 2 above that, compared with Example 1, since no polymer is formed in the inner pores of the carrier to occupy the internal channels in advance, the active components are distributed in all spaces of the carrier channels. Affected by the diffusion limitation of the reaction, the acrylic acid conversion rate is lower than 80%.
[0160] Compared with Example 2, in Comparative Example 2, since in step (2), the molar number of 4,4"-diaminoquaternaryl is 0.9 times the molar number of tri(4-formylphenyl)amine, that is, the number of molecules of the second monomer is insufficient, the synthesis of the organic cage cannot be carried out to the end, the size of the synthesized organic cage is small, and the size distribution is wide, that is, the size of the final part of the active center is not within the optimal range, and there is no activity, so the overall activity of the catalyst is low, and some monomers that are not hydrogenated stay on the catalyst for too long, and polymerization reaction occurs, and the catalyst selectivity is significantly reduced after 1000 hours.
[0161] Compared with Example 3, the second monomer used in Comparative Example 3 is diphenyl diamine, whose molecular size is significantly smaller than 4,4"-diaminoquaternary diamine. The synthesized organic cage is only about 2 nm, which is significantly smaller than the optimal active center size for hydrogenation of acrylic acid. The catalyst activity is low, and some monomers that are not hydrogenated stay on the catalyst for too long, resulting in polymerization reaction. After 1000 hours, the catalyst selectivity decreases more than that of Comparative Example 2.
[0162] In Comparative Example 4, the temperature was too high during the polymerization of lactic acid, resulting in the decomposition of part of the synthesized polylactic acid. The organic cage synthesis was carried out in most of the space inside the carrier. The distribution range of the organic cage, that is, the active center, in the carrier was too wide, and the diffusion effect was obvious in the hydrogenation reaction, resulting in poor activity selectivity.
[0163] Compared with Example 5, since the conventional catalyst preparation method is adopted in Comparative Example 5, and the size distribution of the active centers of the catalyst prepared by the conventional method is wide, the initial activity selectivity of the catalyst is significantly lower than that of the catalyst prepared in Example 5. After 1000 hours, the decrease in its activity selectivity is more obvious than that of the catalyst in Example 5.
[0164] Compared with Example 6, in step (4) of Comparative Example 6, due to the low calcination temperature, the polylactic acid cannot be completely decomposed, which blocks the pores of the catalyst and prevents the reaction materials from diffusing through the pores. Only a small number of active centers on the outer surface of the catalyst participate in the reaction. The reaction molecules entering the pores cannot diffuse and flow, and saturated hydrogenation occurs. Therefore, their activity selectivity is very low.
[0165] In Comparative Example 7, since the organic cage exists alone and is not loaded, although there are porcelain balls and screens on the upper and lower parts of the reactor, the gaps are relatively large. For example, the pore size of the 40-mesh screen is 0.6 mm, while the size of the organic cage is only at the nm level. Therefore, as long as the material is introduced, the organic cage and the palladium active component therein are carried into the subsequent part by the material, and there is no catalyst in the reactor after 24 hours. The hydrogenation rate of acrylic acid is 0.
[0166] The above embodiments are typical examples listed to illustrate the technical solutions of the present invention in detail. The present invention is subject to the protection scope of the claims and the content of the invention and is not limited by the implementation scheme. Simple replacement or modification of the present invention is still within the protection scope of the present invention.
Claims
1. An acrylic acid hydrogenation catalyst, characterized in that: The active component includes Pd, and the carrier is silica gel or mainly silica gel; the outer surface of the carrier has an organic cage with a regular structure, the active component is uniformly loaded in the organic cage, and the cage cavity size of the organic cage is 2.7 to 3.6 nm; The specific surface area of the acrylic acid hydrogenation catalyst is 50 to 100 m 2 / g, based on 100% by mass of the acrylic acid hydrogenation catalyst, the Pd content is 0.2% to 0.4%.
2. The acrylic acid hydrogenation catalyst according to claim 1, characterized in that The organic cage is located within 0.08 mm extending from the outer surface of the carrier toward the center.
3. The acrylic acid hydrogenation catalyst according to claim 1, characterized in that The organic cage is prepared by an aldehyde-amine condensation reaction between an aromatic diamine compound and tri(4-formylphenyl)amine; and the aromatic diamine compound is selected from 4,4"-diaminoquaternaryl, or 4,4"-diaminoquaternaryl substituted by Rm, and the Rm is selected from at least one of halogen, C1-C5 straight chain or linear alkyl.
4. A method for preparing the acrylic acid hydrogenation catalyst according to any one of claims 1 to 3, characterized in that: The steps include: 1) completely polymerizing the hydrophilic polymerizable monomer in the pores of the carrier without decomposing the generated polymer, and controlling the polymer to occupy more than 80% of the pore volume of the carrier to obtain a semi-finished catalyst A; 2) dissolving tri(4-formylphenyl)amine and a catalyst in a solvent, and mixing the mixture with the semi-finished catalyst A to obtain a mixture; adding a solution of an aromatic diamine compound dropwise to the mixture to carry out an aldehyde-amine condensation reaction to form an organic cage, and after the reaction is completed, washing and drying to obtain a semi-finished catalyst B; 3) under stirring, dripping a solution of an organic palladium compound into a mixture of the semi-finished catalyst B and an alcohol, and after the organic palladium compound is completely loaded, washing, drying, and calcining at ≤400° C. to completely decompose the polymer, thereby obtaining a semi-finished catalyst C; 4) mixing the semi-finished catalyst C with a reducing agent, and after the palladium is completely reduced, washing and drying to obtain an acrylic acid hydrogenation catalyst; Wherein, the molar ratio of the tri(4-formylphenyl)amine to the aromatic diamine compound is 1:1.1-2.
2.
5. The preparation method according to claim 4, characterized in that: The mass ratio of palladium in the organic palladium compound to the tri(4-formylphenyl)amine is 2 to 14:
1.
6. The preparation method according to claim 4, characterized in that: In step 1), the volume of the hydrophilic polymerizable monomer is 80%-100% of the pore volume of the carrier, preferably 80%-95%.
7. The preparation method according to claim 4, characterized in that: In step 1), the hydrophilic polymerizable monomer is selected from organic compounds containing a carbonyl group, a carboxyl group or a carbon-carbon double bond. Preferably, the hydrophilic polymerizable monomer is selected from acrylic acid, acrylic acid ester or lactic acid.
8. The preparation method according to claim 4, characterized in that: In step 2), the catalyst is a halogenated acetic acid, preferably fluoroacetic acid or chloroacetic acid, more preferably trifluoroacetic acid or dichloroacetic acid; and / or In step 2), the mass ratio of the tri(4-formylphenyl)amine to the catalyst is 2000-6000:
1.
9. The preparation method according to claim 4, characterized in that: In step 3), the organic palladium compound is selected from palladium acetate or palladium acetylacetonate.
10. The preparation method according to claim 4, characterized in that: In step 4), the semi-finished catalyst C is mixed with a solvent and then mixed with the reducing agent.
Citation Information
Patent Citations
Hydrogenation catalyst, and preparation method and application thereof in hydrogenation of p-tert-butyl phenol
CN111203217A
Production method for synthesizing propionic acid through one-step hydrogenation
CN114230453A
Method for preparing propionic acid through acrylic acid hydrogenation
CN114644552A
Preparation method and application of palladium cluster catalyst
CN114160196A
Preparation method and application of water-soluble organic cage confinement supported rhodium cluster catalyst
CN115301286A